FAKTOR BRANDING PARIWISATA HALAL YANG MEMPENGARUHI PENINGKATAN JUMLAH KUNJUNGAN WISATAWAN KE PULAU LOMBOK - Widayanti, Baiq Harly; Khatami, Ikhzam; Andhika, Dimas Arya; Anggriyani, Anggi; Efendi, Muhammad Haikal (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The number of visits to tourist can be increased through the improvement of supporting facilities. The development of tourism areas requires supporting infrastructure, promotion in marketing tourist objects, and easy accessibility. Marketing tourism products is the same as other products that require branding so that they are easily recognized and remembered by consumers. Lombok Island is famous for its halal tourism branding and currently many locations in Indonesia are also developed with halal branding. The aim of this research is to determine the factors that influence tourist interest in visiting Lombok Island. The analysis method uses multiple linear regression. The number of respondents collected was 113 people with random sampling data collection techniques. The results of this research explain that the halal service variable (X1), travel experience (X3), satisfaction (X4), and loyalty (X5) have a negative sign, which means that this variable has a weak influence on increasing the number of visits. the variable that has a strong influence in increasing the number of visits based on the results of this study is the halal product service variable (X2). The results of this research are consistent with information from the NTB Provincial Tourism Office, which indicates that the current paradigm of halal tourism focuses more on the provision of halal products. Increasing the number of halal-certified products can help boost tourist visits to Lombok Island. Halal-certified MSME products, halal-certified restaurants are very important in supporting the development of tourism on the island of Lombok.